PELAYANAN KESEHATAN DAN PEMBERIAN INFORMASI OBAT PADA PROGRAM DESA BINAAN DI KELURAHAN TATAH LAYAP KABUPATEN BANJAR - Mochammad Maulidie Alfiannor Saputera; Yugo Susanto; Amaliyah Wahyuni; Riza Alfian; Abdul Mahmud Yumassik (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Health services are services in order to improve or maintain health status through prevention efforts with health check activities. The purpose of community service is to improve the health status of the community which is carried out in Tatah Layap Village, Banjar Regency. Tatah Layap Village is a village assisted bySTIKES ISFI Banjarmasin since 2018. This program utilizes the involvement of several medical personnel such as doctors, nurses and pharmacists. The number of health service participants who took part in this activity was 130 people. The method used in this community service is direct health services with health checks for cholesterol, uric acid, blood sugar, high blood pressure and other health checks. Participants took part in this activity starting with registration, then health screening carried out by nurses and getting the results of the initial screening. After doing the initial screening, the doctor will do an examination and get an assessment. Then after the participants get an assessment, the participants go the pharmacy, where participants get drugs and education in the use of drugs that are good, appropriate and correct.